Strategies To Increase Micro, Small And Medium Business Income (MSMEs) Through A Digital Payment System (Case Study of UMKM Sukowono District Jember Regency) - Romadani, Nadia Putri; Hasanah, Miftahul; Syafi’i, Muhammad (Yayasan Rahmat Islamiyah, 2025)
This research aims to analyze the income enhancement strategies of Micro, Small, and Medium Enterprises (MSMEs) through the implementation of digital payment systems in Sukowono District, Jember Regency. In the digital era, the use of cashless payment methods such as QRIS, mobile banking, and e-wallets has become an important factor in increasing transaction efficiency and expanding market access for MSMEs. The research method used is a descriptive qualitative approach with interview techniques directed at MSME actors. The research findings indicate that although digitalization brings significant benefits such as ease of transactions and increased revenue, MSME actors still face various obstacles such as limited internet access, a mindset of the society that is still accustomed to cash transactions, and a lack of understanding of technology. Effective strategies to address these challenges include digitalization training, improving financial literacy, collaborating with financial institutions, and optimizing digital media for marketing.